2019
DOI: 10.1080/17483107.2019.1568594
|View full text |Cite
|
Sign up to set email alerts
|

A review of gait disorders in the elderly and neurological patients for robot-assisted training

Abstract: Arabia. He is currently working towards the Ph.D. degree in the School of Mechanical Engineering,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 61 publications
(198 reference statements)
0
4
0
Order By: Relevance
“…The age presents multicolinearity, mainly when compared with heart, respiratory, rheumatic and hospitalized diseases, not justifying its analysis in the model. Given this context, it is known that gait and its spatiotemporal parameters tend to change over the years and with some diseases 5,6,31 . Some authors have demonstrated a physiological loss, including in gait speed, inherent to the aging process 12,31 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The age presents multicolinearity, mainly when compared with heart, respiratory, rheumatic and hospitalized diseases, not justifying its analysis in the model. Given this context, it is known that gait and its spatiotemporal parameters tend to change over the years and with some diseases 5,6,31 . Some authors have demonstrated a physiological loss, including in gait speed, inherent to the aging process 12,31 .…”
Section: Discussionmentioning
confidence: 99%
“…Given this context, it is known that gait and its spatiotemporal parameters tend to change over the years and with some diseases 5,6,31 . Some authors have demonstrated a physiological loss, including in gait speed, inherent to the aging process 12,31 . Thus, given the multicollinearity of age with the independent variables analyzed, we suggest future studies with longitudinal and mediation analyses to verify the magnitude of age influence.…”
Section: Discussionmentioning
confidence: 99%
“…Further basic and applied research and clinical indications are needed [52]. Analyzes of the required support in people with different types and degrees of deficits will help advance the design of exoskeletons based on user needs [53]. The physiological mechanisms associated with pain in candidates for wearing soft exoskeletons differ between healthy individuals and patients with chronic pain.…”
Section: Discussionmentioning
confidence: 99%
“…Gait deviations leading to changes in spatiotemporal, kinematic, and kinetic gait parameters are common in neurological patients and have a significant influence on everyday life [ 1 , 2 ]. Due to the high impact of walking abilities on participation in daily activities and quality of life, gait recovery in neurological patients is essential [ 3 ], and socioeconomically highly relevant in public health.…”
Section: Introductionmentioning
confidence: 99%